2016
DOI: 10.3892/etm.2016.3211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heart failure on the prognosis of patients with acute myocardial infarction in southwestern China

Abstract: The impact of heart failure (HF) on acute myocardial infarction (AMI) in patients from southwestern China remains unclear. The present study aimed to compare in-hospital cardiovascular events, mortality and clinical therapies in AMI patients with or without HF in southwestern China. In total, 591 patients with AMI hospitalized between February 2009 and December 2012 were examined; those with a history of HF were excluded. The patients were divided into four groups according to AMI type (ST-elevated or non-ST-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Although the treatment of coronary heart disease has made rapid progress, ischemic heart disease induced by coronary artery occlusion is a key cause of morbidity and mortality around the world [1][2][3][4]. At present, treatment with stem cell has a potential effect on cardiovascular regeneration of ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the treatment of coronary heart disease has made rapid progress, ischemic heart disease induced by coronary artery occlusion is a key cause of morbidity and mortality around the world [1][2][3][4]. At present, treatment with stem cell has a potential effect on cardiovascular regeneration of ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term follow-up study revealed that mortality varies according to Killip class, where class 1 had 17.7%, class 2 had 27.3%, class 3 had 30.4%, and class 4 had 48.5% mortality [ 16 ]. This trend indicates that these patients commonly develop pulmonary complications, especially pulmonary edema and congestion, which contribute to the increased mortality rates [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, logistic regression analysis was performed using a backward selection model in the following order: (1) the presence of clinical pharmacists' interventions; and (2) risk factors including age, gender and CCI. 21 Dichotomous variables were expressed as counts (percentage) and were analysed using the χ 2 test or Fisher's exact test. Continuous variables are presented as mean (SD) and were tested using a grouped t test or Wilcoxon rank sum test.…”
Section: Discussionmentioning
confidence: 99%